Pengembangan Multimedia Pembelajaran Bahasa Bali Berbasis Google Sites Untuk Kelas VII Di SMP Negeri 5 Kuta Selatan - Rahayu, Luh Bulaning Dwi (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
This research is based on the low interest of students in the material of orti Bali. Therefore, innovation in more engaging learning media is needed. The aim of this study is to develop multimedia learning for the Balinese language based on Google Sites for seventh-grade students at SMP Negeri 5 Kuta Selatan. The research problems include how to develop multimedia learning for the Balinese language based on Google Sites, the challenges faced, the efforts made during the development process, and the implications of multimedia use on students in cognitive, affective, and psychomotor domains. This study utilizes Richard E. Mayer's cognitive multimedia theory and Edward L. Deci and Richard M. Ryan's self-determination theory. The method used is Research and Development (R&D) following the Borg and Gall model. The development of multimedia learning for the Balinese language based on Google Sites for Balinese orti material at SMP Negeri 5 Kuta Selatan has been successfully implemented and received very good validation from subject matter and media experts, with eligibility percentages of 97.92% and 90.38%, respectively. The challenges faced in the learning process, such as limited teacher time, inadequate facilities, and limited understanding of technology, require a strategic approach to address them. One effective solution is to create a flexible schedule that allows teachers to arrange their teaching time according to the needs of the students. Additionally, training for teachers is crucial to enhance their skills in utilizing educational technology. With proper training, teachers will not only be better prepared to teach but also able to adapt innovative teaching methods. The implications of using this approach are very positive. The improvement in students' cognitive understanding is evident from their academic progress, as they can master the material more effectively. Students' affective motivation also increases, as they feel more engaged and in control of their learning process. Furthermore, students' psychomotor participation in learning, which includes practical skills and social interaction, has also improved. All these factors contribute to the creation of a more dynamic and effective learning environment, which can ultimately produce graduates who are better prepared to face future challenges.